A STUDY ON CLIENT PERCEPTION OF DIGITALIZATION IN BANKING - Pallavi Pahuja (International Journal of Research Science and Management, 2016)
The purpose of this study is to find out what is the basic utility and preference for E banking services provided by banks. The study has been done in Chandigarh city comprising a sample size of 100.After the data collection, researcher has identified which commercial bank provides more quality services with regards to e-banking services to customers and also measured the satisfaction level of customers about internet banking website of banks. The need of the study comes from the fact that, people are too much inclined towards E banking services now a days as it saves time and energy, at the same time there is another set of people who resist internet banking due to certain fears and lack of awareness.